Quality of life in the context of HIV/AIDS: a comparative study with the general population - Silva, Josevânia da; Freire, Francisca Marina de Souza; Lima, Michael Augusto Souza de; Galvão, Jéssica Oliveira; Pichelli, Ana Alayde Werba Saldanha (Brazilian Journal of Sexually Transmitted Diseases, 2013)
Introduction: The introduction of antiretroviral therapy has allowed an increase in life expectancy of HIV-positive patients with HIV/AIDS, characterizing it as a disease amenable to control the long-term, thus influencing well-being and quality of life of these subjects. Objective: To evaluate the perceived quality of life of people with HIV/AIDS compared with that of people without the diagnosis for HIV. Methods: We counted with the participation of 561 people with HIV and 286 people without the diagnosis. Specific socio-demographic and clinical questionnaires, beyond the scale of quality of life WHOQOL-HIV-Bref were applied. Results: The quality of life was assessed positively by 59% of seropositive, being the dimensions spirituality and future prospects the better evaluated. Of the participants with no HIV diagnosis, 61% positively evaluated the quality of life, being the dimensions spirituality and independence the better evaluated. Regarding the domains of quality of life, both groups showed positive evaluation for all dimensions. However, the seropositive group evaluated more negatively the domains environmental and independence compared to the group without diagnosis. Conclusion: Results suggest that the diagnosis of HIV seropositivity is not a sufficient condition for the perception of quality of life to differ from people in general. Moreover, the less positive assessment on health for HIV-positive group seems to indicate that, for these subjects, health is related to aspects associated with organic etiologies and the psychosocial consequences of living with HIV/AIDS.